A Group Recommendation System of Network Document Resource Based on Knowledge Graph and LSTM in Edge Computing. (2nd December 2020) - Wu, Yuezhong; Liu, Qiang; Chen, Rongrong; Li, Changyun; Peng, Ziran
Abstract : The Internet has become one of the important channels for users to obtain information and knowledge. It is crucial to work out how to acquire personalized requirement of users accurately and effectively from huge amount of network document resources. Group recommendation is an information system for group participation in common activities that meets the common interests of all members in the group. This paper proposes a group recommendation system for network document resource exploration using the knowledge graph and LSTM in edge computing, which can solve the problem of information overload and resource trek effectively. An extensive system test has been carried out in the field of big data application in packaging industry. The experimental results show that the proposed system recommends network document resource more accurately and further improves recommendation quality using the knowledge graph and LSTM in edge computing. Therefore, it can meet the user's personalized resource need more effectively.